Are novel or locally adapted pathogens more devastating and why? Resolving opposing hypotheses - Erin L. Sauer; Matthew D. Venesky; Taegan A. McMahon; Jeremy M. Cohen; Scott Bessler; Laura A. Brannelly; Forrest Brem; Allison Q. Byrne; Neal Halstead; Oliver Hyman; Pieter T. J. Johnson; Corinne L. Richards‐Zawacki; et al. (Ecology Letters, 2024)
There is a rich literature highlighting that pathogens are generally better adapted to infect local than novel hosts, and a separate seemingly contradictory literature indicating that novel pathogens pose the greatest threat to biodiversity and public health. Here, using Batrachochytrium dendrobatidis , the fungus associated with worldwide amphibian declines, we test the hypothesis that there is enough variance in “novel” (quantified by geographic and phylogenetic distance) host‐pathogen outcomes to pose substantial risk of pathogen introductions despite local adaptation being common. Our continental‐scale common garden experiment and global‐scale meta‐analysis demonstrate that local amphibian‐fungal interactions result in higher pathogen prevalence, pathogen growth, and host mortality, but novel interactions led to variable consequences with especially virulent host‐pathogen combinations still occurring. Thus, while most pathogen introductions are benign, enough variance exists in novel host‐pathogen outcomes that moving organisms around the planet greatly increases the chance of pathogen introductions causing profound harm.

Fire severity effects on the herpetofaunal diversity of the Florida scrub, a biodiversity hotspot - Michelle N. Lindsay; David B. Lewis; Neal Halstead; Alison M. Gainsbury (Biodiversity and Conservation, 2023)

A meta‐analysis reveals temperature, dose, life stage, and taxonomy influence host susceptibility to a fungal parasite - Erin L. Sauer; Jeremy M. Cohen; Marc J. Lajeunesse; Taegan A. McMahon; David J. Civitello; Sarah A. Knutie; Karena Nguyen; Elizabeth A. Roznik; Brittany F. Sears; Scott Bessler; Bryan K. Delius; Neal Halstead; et al. (Ecology, 2020)
Complex ecological relationships, such as host–parasite interactions, are often modeled with laboratory experiments. However, some experimental laboratory conditions, such as temperature or infection dose, are regularly chosen based on convenience or convention, and it is unclear how these decisions systematically affect experimental outcomes. Here, we conducted a meta‐analysis of 58 laboratory studies that exposed amphibians to the pathogenic fungus Batrachochytrium dendrobatidis (Bd) to understand better how laboratory temperature, host life stage, infection dose, and host species affect host mortality. We found that host mortality was driven by thermal mismatches: hosts native to cooler environments experienced greater Bd‐induced mortality at relatively warm experimental temperatures and vice versa. We also found that Bd dose positively predicted Bd‐induced host mortality and that the superfamilies Bufonoidea and Hyloidea were especially susceptible to Bd. Finally, the effect of Bd on host mortality varied across host life stages, with larval amphibians experiencing lower risk of Bd‐induced mortality than adults or metamorphs. Metamorphs were especially susceptible and experienced mortality when inoculated with much smaller Bd doses than the average dose used by researchers. Our results suggest that when designing experiments on species interactions, researchers should carefully consider the experimental temperature, inoculum dose, and life stage, and taxonomy of the host species.

Effects of pesticides on exposure and susceptibility to parasites can be generalised to pesticide class and type in aquatic communities - Samantha L. Rumschlag; Neal T. Halstead; Jason T. Hoverman; Thomas R. Raffel; Hunter J. Carrick; Peter J. Hudson; Jason R. Rohr (Ecology Letters, 2019)
Pesticide pollution can alter parasite transmission, but scientists are unaware if effects of pesticides on parasite exposure and host susceptibility (i.e. infection risk given exposure) can be generalised within a community context. Using replicated temperate pond communities, we evaluate effects of 12 pesticides, nested in four pesticide classes (chloroacetanilides, triazines, carbamates organophosphates) and two pesticide types (herbicides, insecticides) applied at standardised environmental concentrations on larval amphibian exposure and susceptibility to trematode parasites. Most of the variation in exposure and susceptibility occurred at the level of pesticide class and type, not individual compounds. The organophosphate class of insecticides increased snail abundance (first intermediate host) and thus trematode exposure by increasing mortality of snail predators (top–down mechanism). While a similar pattern in snail abundance and trematode exposure was observed with triazine herbicides, this effect was driven by increases in snail resources (periphytic algae, bottom–up mechanism). Additionally, herbicides indirectly increased host susceptibility and trematode infections by (1) increasing time spent in susceptible early developmental stages and (2) suppressing tadpole immunity. Understanding generalisable effects associated with contaminant class and type on transmission is critical in reducing complexities in predicting disease dynamics in at‐risk host populations.

Impacts of thermal mismatches on chytrid fungus Batrachochytrium dendrobatidis prevalence are moderated by life stage, body size, elevation and latitude - Jeremy M. Cohen; Taegan A. McMahon; Chloe Ramsay; Elizabeth A. Roznik; Erin L. Sauer; Scott Bessler; David J. Civitello; Bryan K. Delius; Neal Halstead; Sarah A. Knutie; Karena H. Nguyen; Nicole Ortega; et al. (Ecology Letters, 2019)
Global climate change is increasing the frequency of unpredictable weather conditions; however, it remains unclear how species‐level and geographic factors, including body size and latitude, moderate impacts of unusually warm or cool temperatures on disease. Because larger and lower‐latitude hosts generally have slower acclimation times than smaller and higher‐latitude hosts, we hypothesised that their disease susceptibility increases under ‘thermal mismatches’ or differences between baseline climate and the temperature during surveying for disease. Here, we examined how thermal mismatches interact with body size, life stage, habitat, latitude, elevation, phylogeny and International Union for Conservation of Nature (IUCN) conservation status to predict infection prevalence of the chytrid fungus Batrachochytrium dendrobatidis ( Bd ) in a global analysis of 32 291 amphibian hosts. As hypothesised, we found that the susceptibility of larger hosts and hosts from lower latitudes to Bd was influenced by thermal mismatches. Furthermore, hosts of conservation concern were more susceptible than others following thermal mismatches, suggesting that thermal mismatches might have contributed to recent amphibian declines.

Community ecology theory predicts the effects of agrochemical mixtures on aquatic biodiversity and ecosystem properties - Neal T. Halstead; Taegan A. McMahon; Steve A. Johnson; Thomas R. Raffel; John M. Romansic; Patrick W. Crumrine; Jason R. Rohr (Ecology Letters, 2014)
Ecosystems are often exposed to mixtures of chemical contaminants, but the scientific community lacks a theoretical framework to predict the effects of mixtures on biodiversity and ecosystem properties. We conducted a freshwater mesocosm experiment to examine the effects of pairwise agrochemical mixtures [fertiliser, herbicide (atrazine), insecticide (malathion) and fungicide (chlorothalonil)] on 24 species‐ and seven ecosystem‐level responses. As postulated, the responses of biodiversity and ecosystem properties to agrochemicals alone and in mixtures was predictable by integrating information on each functional group's (1) sensitivity to the chemicals (direct effects), (2) reproductive rates (recovery rates), (3) interaction strength with other functional groups (indirect effects) and (4) links to ecosystem properties. These results show that community ecology theory holds promise for predicting the effects of contaminant mixtures on biodiversity and ecosystem services and yields recommendations on which types of agrochemicals to apply together and separately to reduce their impacts on aquatic ecosystems.

Fungicide‐induced declines of freshwater biodiversity modify ecosystem functions and services - Taegan A. McMahon; Neal T. Halstead; Steven Johnson; Thomas R. Raffel; John M. Romansic; Patrick W. Crumrine; Jason R. Rohr (Ecology Letters, 2012)
Although studies on biodiversity and ecosystem function are often framed within the context of anthropogenic change, a central question that remains is how important are direct vs. indirect (via changes in biodiversity) effects of anthropogenic stressors on ecosystem functions in multitrophic‐level communities. Here, we quantify the effects of the fungicide chlorothalonil on 34 species‐, 2 community‐ and 11 ecosystem‐level responses in a multitrophic‐level system. At ecologically relevant concentrations, chlorothalonil increased mortality of amphibians, gastropods, zooplankton, algae and a macrophyte (reducing taxonomic richness), reduced decomposition and water clarity and elevated dissolved oxygen and net primary productivity. These ecosystem effects were indirect and predictable based on changes in taxonomic richness. A path analysis suggests that chlorothalonil‐induced reductions in biodiversity and top‐down and bottom‐up effects facilitated algal blooms that shifted ecosystem functions. This work emphasises the need to re‐evaluate the safety of chlorothalonil and to further link anthropogenic‐induced changes in biodiversity to altered ecosystem functions.

Parasitism in a community context: trait‐mediated interactions with competition and predation - Thomas R. Raffel; Jason T. Hoverman; Neal T. Halstead; Patrick J. Michel; Jason R. Rohr (Ecology, 2010)
Predation and competition can induce important density‐ and trait‐mediated effects on species, with implications for community stability. However, interactions of these factors with parasitism remain understudied. Here we investigate interactions among competition, predation and parasitism by crossing tadpole density ( Bufo americanus ), presence of a caged predator ( Notophthalmus viridescens ), and Echinostoma trivolvis trematodes, experimentally partitioning their effects on tadpole exposure and susceptibility to infection. Predation did not affect E. trivolvis infection but accelerated tadpole development and growth, and decreased activity. The presence of E. trivolvis caused the opposite effects on these three responses and reduced tadpole survival. High conspecific density reduced tadpole survival, growth, and development, and increased tadpole activity. Effects of predation and parasitism on activity were only evident at low tadpole density. High‐density mesocosms also had twice the number of E. trivolvis infections as low‐density mesocosms, despite a lack of evidence for stress‐induced immunomodulation. Instead, this effect was explained by high density delaying tadpole development, which increased both the duration of exposure to cercariae and susceptibility to infection, because tadpoles spent more time in highly susceptible early stages. These results highlight the importance of accounting for trait‐mediated effects, host plasticity, and exposure vs. susceptibility in parasite ecology.